Pet ownership: Their interactions towards pets and perceptions of animal welfare in zoos - Majid, Muhammad Aulia (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Pets play an important role in human life. Many studies have shown that the presence of pets can improve the physical and mental health of their owners. The relationship between owners and pets tends to result in more positive behavior from owners towards other animals. Zoos are one of the locations where humans interact with various animals. The presence of humans (visitors) in zoos harms animal welfare in that location. Therefore, this study aims to determine the effect of pet ownership on perceptions of animal welfare in zoos. Methods: This study uses a quantitative method that examines the impact of pet ownership on perceptions of animal welfare in zoos. Through quantitative methods, a survey was conducted to collect data on public perceptions, both pet owners and non-owners, to see their perceptions of animal welfare in zoos. Findings: The study's results revealed that pet owners had higher HAIS values ​​than those who did not have pets. Then the perception of animal welfare in general showed that pet owners tended to have lower perceptions of animal welfare than non-pet owners. The relationship between the level of relationship closeness between humans and pets and the perception of animal welfare showed a low negative correlation, which means that the higher the HAIS value, the lower the perception of welfare towards zoo animals. Pet owners tend to be more sensitive to the conditions of animals that are less than ideal. The following research reveals that positive human interactions with pets will encourage positive behavior toward other animals. Conclusion: This study concludes that pet owners have a more critical perception of animal welfare in zoos than visitors who do not have pets. The level of closeness of interaction also influences the critical behavior of pet owners towards animal welfare conditions in zoos. Novelty/Originality of this article: The novelty of this study lies in identifying the perceptions of zoo visitors through their level of interaction with pets. This study is unique because it uses the closeness level of interaction with pets to see the zoo visitor's perceptions of animal welfare in zoos.